The General Inspector Supervision in Fighting the Financial and Administrative Corruption (مجلة المنصور, 2022)
The Financial and Administrative Phenomenon is considered one of those phenomena that are recently spread among the world countries especially the developing countries because of the fact that the Executive Administrative Authorities are not complying with the clear and accurate legislations, and that they are not following the transparent regulations through which supervisioncan be conducted, in one hand, and the individuals negligence and their fair that resulted from the lack of freedom in the other hand.The research problem is summarized in the fact that corruption is not resulted only by the Political Authority, but it has another partner which is represented by the Private Boards, which made everybody responsible about this hatful phenomenon. Everybody knows that corruption results cause social and economic losses because it leads to hindering development projects,prosperity achievement, weakening the democratic construction and affecting the Institutions State.The research aim is represented by the fact that supervision will lead to fighting the Financial and Administrative Corruption which badly affect society and economy. On the other hand, to remove all barricades that hinders the achievement of the people prosperity in addition to enhancing the supervision of the Institutions States Construction and strengthening the DemocraticFoundation.The subject was discussed in three demands, the first was to identify the General Inspector, and the second will discuss the Legal Nature of the General Inspector, while the third will be dedicated to show the actions and methods of the General Inspector's Tasks, which will be discussed successively .